Sosialisasi Memertahankan Zero Stunting yang Ditaja Oleh Mahasiswa Kukerta Unri 2023 di Desa Simpang Perak Jaya - Tantri Puspita Yazid; Rahman Wahyudhi; Miftah Hilmi Hairani Lubis; Vera Wandira; Halfina Syuhada; Gilang Yuda Nardana; Selvy Apriyani; Adhisty Shenia Auliandri Putri; Regita Marselina; Indy Titania (FKIP, Universitas Palangka Raya, 2023)
Indonesia's vision for 2020-2024 is to focus on developing human resources starting from development in the health sector. Priority programs in the Health sector include maternal and toddler/child health. Stunting is a hot issue and urgent to be resolved because it has an impact on the quality of Indonesia's human resources in the future. Human resources are the main factor in determining the success of a country and nation. The aim of writing the article is to socialize maintaining zero stunting which was initiated by Kukerta UNRI students in Simpang Perak Jaya village. The research method used is a qualitative approach with descriptive analysis. The data source is an analysis of policy documents. Stunting is defined as a height index for age (TB/U) less than the 3rd percentile. Kukerta UNRI in Simpang Perak Jaya Village, through this activity, took the initiative to carry out socialization activities to maintain zero stunting with the aim of increasing the community's knowledge and knowledge regarding stunting. The implementation of stunting socialization goes through 3 stages, namely preparing facilities and infrastructure, the socialization stage and the evaluation stage. The result of the implementation of this socialization on maintaining zero stunting is an increase in the knowledge of the Simpang Perak Jaya Village community after being given counseling in the form of socialization.